Troublesome young men : the rebels who brought Churchill to power and helped save England - Olson, Lynne (New York : Farrar, Straus and Giroux, 2007)
Describes how, in 1940, a group of rebellious Tory members of Parliament defied the appeasement policies of British Prime Minister Neville Chamberlain to force his resignation and bring to power Winston Churchill
"We may be going to die" -- Playing the game -- "Troublesome young men" -- "Dictators are very popular these days" -- "I lack the 'spunk'" -- "Quite simply, he told lies" -- "Our own soul is at stake" -- "'Terrible, unmitigated, unparalleled dishonor'" -- Retribution -- "Waiting for a stirring lead" -- "Here is the testing" -- "Speak for England" -- Playing at war -- "The misery of doing nothing" -- "He is absolutely loyal" -- "Gambling with the life of the nation" -- "'In the name of God, go!" -- "Victory at all costs" -- A question of loyalty -- A son's betrayal
Includes bibliographical references (pages 403-411) and index
Keywords: Churchill, Winston, -- 1874-1965; Chamberlain, Neville, -- 1869-1940; Conservative Party (Great Britain); Great Britain -- Politics and government -- 1936-1945